PEMBENTUKAN SIKAP SOSIAL SISWA DALAM PEMBELAJARAN IPS (Studi Kualitatif Deskriptif di SMP Negeri 22 Bandar Lampung) - ., Sujarwo (Lentera: Jurnal Ilmiah Kependidikan, 2014)
Social attitudes is an important thing in life together in a society. This is because during his life humans will never be separated in the presence of an interaction with another human being. With a good social interaction is expected to lead to social feelings that can bind the individual to his fellow human beings in the form of mutual help, respect and accept, sympathy, and so on.Social Studies has the noble task as the foundation of the development potential of learners, intellectually, socially, culturally and socially, which is able to foster a way of thinking, attitude and behavior are responsible as individuals, citizens, and citizens as well as citizens of the world. Additionally Sciences also has the task of developing social values in shaping social attitudes of learners in the face of social problems, both of which draw themselves and society that occur in everyday life.Teachers are required to demonstrate high creativity in developing learning in the classroom, and is expected to achieve breakthrough in social studies learning, so that learning becomes meaningful learning undertaken. Learning that promotes mastery of competencies focus on learners, provide learning and provide learning experiences relevant and contextualized subject matter and develop a rich and strong mentally to students.